2017
DOI: 10.1007/s12350-016-0467-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex affects myocardial blood flow and fatty acid substrate metabolism in humans with nonischemic heart failure

Abstract: In animal models of heart failure (HF), myocardial metabolism shifts from the normal preference for high-energy fatty acid (FA) metabolism towards the more efficient fuel, glucose. However, FA (vs. glucose) metabolism generates more ATP/mole; thus FA metabolism may be especially advantageous in HF. Sex modulates myocardial blood flow (MBF) and substrate metabolism in normal humans. Whether sex affects MBF and metabolism in patients with HF is unknown. We studied 19 well-matched men and women with nonischemic H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…16 Indeed, this sexual dimorphism persists, at least for myocardial FA metabolism in patients with HFrEF due to non-ischemic origin. 17 Age is also a critical determinant in myocardial substrate utilization with an increasing dependence on MGU with advancing age. 18 Obesity is another patient attribute that needs to be considered when assessing cardiac metabolic activity.…”
Section: See Related Article Pp 585-597mentioning
confidence: 99%
“…16 Indeed, this sexual dimorphism persists, at least for myocardial FA metabolism in patients with HFrEF due to non-ischemic origin. 17 Age is also a critical determinant in myocardial substrate utilization with an increasing dependence on MGU with advancing age. 18 Obesity is another patient attribute that needs to be considered when assessing cardiac metabolic activity.…”
Section: See Related Article Pp 585-597mentioning
confidence: 99%
“…For instance, a large [ 18 F]-FDG PET study consisting of 493 men and 470 women spanning 5 decades (32 – 87 years) showed lower metabolism in parietal cortex for men compared to women, while lower metabolism was observed in ventrolateral prefrontal cortex for women compared to men [215]. In a multi-institutional study of nonischemic heart failure, three radiotracers, [ 15 O]-H 2 O, [ 11 C]-palmitate and [ 11 C]-glucose, were used to evaluate myocardial blood flow and metabolism [216]. Findings indicated that sex, but not other variables such as age, was associated with the higher blood flow and fatty acid metabolism observed in women, while glucose metabolism did not differ appreciably between the sexes.…”
Section: Preclinical Imagingmentioning
confidence: 99%
“…In order to slow down the progression of DKD, recognizing patients with a high risk at an early stage is important. Sex differences have been taken into account in development or progression in several diseases such as diabetes [3] , chronic kidney disease (CKD) [4] , heart failure [5] , and neuropsychiatric disorders [6] . Recently, a study from the Chronic Renal Insufficiency Cohort that included 3939 adults (half of them had diabetes) showed that male had the higher risk of CKD progression and death compared with female patients [4] .…”
Section: Introductionmentioning
confidence: 99%